2018
DOI: 10.1038/s41467-018-04366-7
|View full text |Cite
|
Sign up to set email alerts
|

Single cell analysis of kynurenine and System L amino acid transport in T cells

Abstract: The tryptophan metabolite kynurenine has critical immunomodulatory properties and can function as an aryl hydrocarbon receptor (AHR) ligand. Here we show that the ability of T cells to transport kynurenine is restricted to cells activated by the T-cell antigen receptor or proinflammatory cytokines. Kynurenine is transported across the T-cell membrane by the System L transporter SLC7A5. Accordingly, the ability of kynurenine to activate the AHR is restricted to T cells that express SLC7A5. We use the fluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
106
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(119 citation statements)
references
References 36 publications
(49 reference statements)
5
106
0
Order By: Relevance
“…In corroboration with these data, we also observed increased amounts of transcripts related to the ASC survival or differentiation, such as TNFS13B and IL-10 ( Supplementary Figure 5) as previously described (30,(73)(74)(75). Thus, it is suggested that the tryptophan degradation would be the cause and not consequence of the DENV-mediated ASC differentiation in vitro, as it seems to occur earlier than the BLIMP1 expression (64). The role of this metabolic pathway in the massive ASC response detected in Dengue patients is still to be ascertained.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In corroboration with these data, we also observed increased amounts of transcripts related to the ASC survival or differentiation, such as TNFS13B and IL-10 ( Supplementary Figure 5) as previously described (30,(73)(74)(75). Thus, it is suggested that the tryptophan degradation would be the cause and not consequence of the DENV-mediated ASC differentiation in vitro, as it seems to occur earlier than the BLIMP1 expression (64). The role of this metabolic pathway in the massive ASC response detected in Dengue patients is still to be ascertained.…”
Section: Discussionsupporting
confidence: 90%
“…Genes with expressions tightly bound to the IDO activity, such as eukaryotic initiation factor 2 alpha (eIF2alpha) and kinase general control non-derepressible-2 (GCN2), can enhance the BLIMP1 (or PRDM1) expression in a tryptophan-depleted condition. On the other hand, the BLIMP1 protein binds to the IDO promoter, repressing its expression (64). The tryptophan degradation also modifies the expression of SLC7A5 (65) and WARS during this process in cancer cells (66) and ASCs (67).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it was of interest to determine whether the availability of Asn impinged upon T cell metabolism. The tryptophan metabolite kynurenine is transported into T cells via the neutral amino acid transporter Slc7a5/CD98 (21), that also serves as a transporter for essential amino acids tryptophan, leucine, phenylalanine and methionine. We took advantage of the fluorescent properties of kynurenine as well as the glucose analog 2-NB-d-glucose and long chain fatty acid analog BODIPY TM C16 to assess the impact of amino acid deprivation on TCR-induced nutrient uptake.…”
Section: Asn Availability Regulates Tcr-induced Metabolic Reprogrammingmentioning
confidence: 99%
“…Accordingly, we examined the impact of Myc expression on the functional capacity of T cells to transport amino acids and we assessed whether the loss of amino acid transporter expression could recapitulate the striking impact of Myc deletion on T cell protein production. We focused on the system L transporter Slc7a5, as this is the most abundant amino acid transporter expressed on immune activated T lymphocytes ( Fig 3A, 4B, Table S1) and mediates transport of many essential amino acids including methionine, leucine, phenylalanine and tryptophan (Sinclair et al, 2019;Sinclair, Neyens, Ramsay, Taylor, & Cantrell, 2018;Sinclair et al, 2013).…”
Section: Myc Controls Amino Acid Transporter Expression In Immune Actmentioning
confidence: 99%
“…Kynurenine uptake assay were performed as described in (Sinclair et al, 2018). Briefly, antibodies against surface markers were added to culture (37 o C 5% CO2) for 10 minutes prior to uptake assay in order to identify cell types.…”
Section: Kynurenine Uptakesmentioning
confidence: 99%